Preparation of flexible ultraviolet photodetectors based on ZnO film using a dip-coating method on different flexible substrates. (1st September 2022) - Hui, Yifan; Ren, Yuxin; Song, Jiaming; Hu, Peng; Fan, Haibo; Teng, Feng
Abstract: Flexible ultraviolet (UV) photodetectors (PDs) have attracted considerable attention owing to their significant potential for application in wearable electronic devices. In this study, flexible UV PDs based on ZnO films were prepared on different flexible substrates by using a simple dip-coating method. The photodetection properties of the PDs were evaluated and analyzed in detail. The results showed that the PD using filter paper as a substrate exhibited higher flexibility and stability than the PDs constructed on polyethylene terephthalate and A4 paper substrates. When the bending angle reached 60°, the PD on filter paper exhibited a significant switch response with response times of 3.83 s and 13.52 s. The excellent flexibility of the PD on filter paper resulted from the loose and porous structure of the ZnO film, which can effectively reduce the influence of substrate bending. This work paves a way toward the research and development of high-performance, wearable, paper-based optoelectronic nanodevices.